Non‐Surgical Periodontal Therapy Reduces Saliva Adipokine and Matrix Metalloproteinase Levels in Periodontitis. Issue 8 (1st August 2016) - Özcan, Erkan; Işıl Saygun, N.; Serdar, Muhittin A.; Umut Bengi, V.; Kantarcı, Alpdoğan
Abstract : Background: Adipokines enhance the synthesis of proinflammatory cytokines and matrix metalloproteinases (MMPs), which play a role in extracellular matrix degeneration. The aim of this study is to determine the levels of some adipokines, proinflammatory cytokines, and MMPs in the saliva of patients with periodontitis and healthy individuals and to evaluate the changes after non‐surgical periodontal therapy (NSPT). Methods: Of 32 individuals included in the study, 17 had periodontitis and 15 had healthy gingiva. Saliva samples were obtained from all individuals. In patients with periodontitis, samples were recollected 3 and 6 months after NSPT. Visfatin, chemerin, progranulin, interleukin (IL)‐1β, IL‐8, MMP‐8, and MMP‐13 levels were measured using enzyme‐linked immunosorbent assay. Results: In patients with periodontitis, all of the parameters measured in the saliva were higher than those of healthy individuals. At 3 months, visfatin, progranulin, IL‐8, and MMP‐8 levels were significantly decreased compared with baseline values. The levels of other biochemical parameters, chemerin and IL‐1β, were significantly decreased compared with baseline values at 6 months, and the levels became similar to those in healthy individuals. In the periodontitis group, positive correlations were found among visfatin and IL‐8 ( r = 0.909, P <0.01), MMP‐8 ( r = 0.702, P = 0.02), and MMP‐13 ( r = 0.781, P = 0.01); chemerin and IL‐8 ( r = 0.913, P <0.01), MMP‐8 ( r = 0.770, P <0.01), and MMP‐13 ( r = 0.788, P <0.01); and progranulin and IL‐8 ( r = 0.762, P <0.01), MMP‐8 ( r = 0.845, P <0.01), and MMP‐13 ( r = 0.813, P <0.01). Conclusion: Adipokines may contribute to the breakdown of periodontal tissue in periodontitis by stimulating the expression of proinflammatory cytokines and MMPs.